Probing the Context of Vulnerability: Zimbabwean Migrant Women's Experiences of Accessing Public Health Care in South Africa (African Human Mobility Review, 2021)
The economic meltdown and worsening levels of poverty in Zimbabwe led to asignificant increase in the number of women migrating to South Africa from 2005 to2010 (Crush et al., 2015: 367). A Southern African Migration Programme (SAMP)survey in 1997 found that 61% of Zimbabwean migrants were male and 39% werefemale (Crush et al., 2015: 367). This suggested that there was an increase in thenumber of women migrating to South Africa compared with other countries inSouthern Africa. This gives us reason to ‘speculate’ that the numbers could haveincreased a decade later because of the economic crisis that resulted in large numbersof people migrating out of Zimbabwe. Most Zimbabwean women are now movingacross borders independently of their spouses and partners in search of better andsustainable livelihoods (Dzingirai et al., 2015: 13; Mbiyozo, 2019). Whilst some havevalid immigration documents, a large number of these women are undocumented,which heightens their vulnerability to various structures of violence (Bloch, 2010;Rutherford, 2020: 172).